Long-term survival outcomes in patients with surgically treated oropharyngeal cancer and defined human papilloma virus status. Issue 11 (8th November 2016) - Dale, O T; Sood, S; Shah, K A; Han, C; Rapozo, D; Mehanna, H; Winter, S C
Abstract: Objective: This study investigated long-term survival outcomes in surgically treated oropharyngeal cancer patients with known human papilloma virus status. Methods: A case note review was performed of all patients undergoing primary surgery for oropharyngeal cancer in a single centre over a 10-year period. Human papilloma virus status was determined via dual modality testing. Associations between clinicopathological variables and survival were identified using a log-rank test. Results: Of the 107 cases in the study, 40 per cent ( n = 41) were human papilloma virus positive. The positive and negative predictive values of p16 immunohistochemistry for human papilloma virus status were 57 per cent and 100 per cent, respectively. At a mean follow up of 59.5 months, 5-year overall and disease-specific survival estimates were 78 per cent and 69 per cent, respectively. Human papilloma virus status ( p = 0.014), smoking status ( p = 0.021) and tumour stage ( p = 0.03) were significant prognostic indicators. Conclusion: The long-term survival rates in surgically treated oropharyngeal cancer patients were comparable to other studies. Variables including human papilloma virus status and tumour stage were associated with survival in patients treated with primary surgery; however, nodal stage and presence of extracapsular spread were non-prognostic.